(untitled) (Journal of Fiber Bioengineering and Informatics, 2015)
Dynamic geometries acquisition of human is one of the most popular topics in the fields of computer vision and computer graphics. This paper presents the related techniques on rapidly generation of human model sequences and makes skinning animation using single Kinect. In specified applied conditions, it has good animation effects and interaction functions. As the comparatively low request on resolution by animation, using the Kinect can greatly save human body animation production time and reduce production cost.